IMPROVING THE QUALITY OF WOMEN'S COOPERATIVE FINANCIAL REPORTS IN THE DISTRICT OF ANTI GRESIK REGENCY WITH ACTION RESERCH APPROACH - Hidayat, Ujang Syaiful (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2022)
The Women's Cooperative (KOPWAN) Bina Citra Wanita is a legal entity cooperative that has a savings and loan business unit. KOPWAN is a form of joint effort based on the principles of kinship and mutual cooperation. However, problems arise when it comes to providing precise and accurate financial reports, in accordance with SAK ETAP (Financial Accounting Standards for Entities Without Public Accountability). These activities require extra work from KOPWAN administrators who double as housewives. This often creates conflicts of its own in dividing the time because the financial statements made are still using conventional methods. This condition is not balanced with the increasing number of activities because the number of members served is increasing. The purpose of this study will be to examine the extent to which the implementation of computerized-based financial reporting with accounting software can improve the quality of KOPWAN financial report information. This study uses an action research approach. The results of the study indicate that Accounting Software is quite effective and efficient in helping management make financial reports quickly, precisely and accurately and reduce fraud. In addition, it is able to save time and energy so that it does not interfere with the activities of mothers in carrying out domestic and public activities. Keywords: action research, SAK ETAP, Accounting Software